PENGARUH KUALITAS PELAYANAN, PROMOSI, REPUTASI DAN LOKASI TERHADAP KEPUTUSAN NASABAH MENABUNG DI PT. BANK MANDIRI (PERSERO) TBK CABANG KROYA - Anggoro Dwi Pramudo; Tri Esti Masita; Heri Setiawan (Majalah Imiah Manajemen & Bisnis, 2020)
Research is called “influence the quality of services, promotion, reputation and location of the decision customers save at PT. Bank Mandiri (Persero) tbk the branch Kroya”. The purpose of this research is to find significance influence the quality of services, promotion, reputation, and location of the decision customers in save at PT. Bank Mandiri (Persero) tbk the branch Kroya. Instrument the analysis used linear regression multiple. From research is it can be concluded: Hypothesis first said the quality of services significant of the decision customers save at PT. Bank Mandiri (Persero) tbk the branch Kroya, with the trust 95 %, accepted. This is proven by test t, t count the quality of services greater than t table (5,070 > 1,9853). Hypothesis second said promotion significant impact on customers save at the PT. Bank Mandiri (Persero) tbk branch Kroya, with the trust % 95, accepted. This is proven by test t, t count promotion greater than t table (3,215 > 1,9853). Hypothesis third said reputation significant of the decision customers save at PT. Bank Mandiri (Persero ) tbk the branch kroya, with the trust 95 %, accepted. This is proven by test t, t count reputation greater than t table (2,049 > 1,9853). Hypothesis fourth said location significant of the decision customers save at PT. Bank mandiri (Persero) tbk the branch kroya, with the trust 95 %, accepted. This is proven by test t, t count location greater than t table (3,709 > 1,9853).